Cross the borders: the dual cultural devaluation of the Belt and Road co-production films - Zhou, Ying (Humanities & social sciences communications, 2025)
Since the inception of the Belt and Road Initiative (BRI) by the Chinese government in 2013, there has been a concerted effort to promote cross-border and cross-cultural communication, with a particular emphasis on the field of Chinese cinema. This article embarks on a comprehensive evaluation of the extent to which co-produced films under the aegis of the BRI have effectively achieved the political and cultural objectives originally outlined by the policy. Moreover, it strives to offer an understanding of the reception and impact of these films in overseas markets. Employing computational textual analysis and visualisation techniques, the study examines the global market performance, online ratings, and critical reviews of BRI co-productions since their inception. Despite a decade of promotion, BRI co-productions have demonstrated limited success on the global stage. A key characteristic that has emerged is cultural discount, which is influenced by political factors, the diminishing artistic aura, and an absence of narrative strategies that emphasise translocality. BRI co-productions encounter dual cultural devaluation, stemming from conflicts between their cultural and political aspirations and the prevailing principles of the global film industry. The study proposes enhancing the quality of co-productions and generating promotional “buzz” as viable strategies to mitigate the loss of artistic prestige and to expand their global reach.